The cost of post-abortion care (PAC): a systematic review - Estro Dariatno Sihaloho; Ibnu Habibie; Fariza Zahra Kamilah; Yodi Christiani (BMC, 2022)
Abstract Background Despite the increasing trend of Postabortion Care (PAC) needs and provision, the evidence related to its cost is lacking. This study aims to review the costs of Postabortion Care (PAC) per patient at a national level. Methods A systematic review of literature related to PAC cost published in 1994 - October 2020 was performed. Electronic databases such as PubMed, Medline, The Cochrane Library, CINAHL, and PsycINFO were used to search the literature. Following the title and abstract screening, reporting quality was appraised using the Consolidates Health Economic Evaluation (CHEERS) checklist. PAC costs were extrapolated into US dollars ($US) and international dollars ($I), both in 2019. Results Twelve studies met the inclusion criteria. All studies reported direct medical cost per patient in accessing PAC, but only three of them included indirect medical cost. All studies reported either average or range of cost. In terms of range, the highest direct cost of PAC with MVA (Medical Vacuum Aspiration) services can be found in Colombia, between $US50.58-212.47, while the lowest is in Malawi ($US15.2-139.19). The highest direct cost of PAC with D&C (Dilatation and Curettage), services is in El Salvador ($US65.22-240.75), while the lowest is in Bangladesh ($US15.71-103.85). Among two studies providing average indirect cost data, Uganda with $US105.04 has the highest average indirect medical cost, while Rwanda with $US51.44 has the lowest. Conclusions Our review shows variability in the cost of PAC across countries. This study depicts a clearer picture of how costly it is for women to access PAC services, although it is still seemingly underestimated. When a study compared the use of UE (Uterine Evacuation) method between MVA and D&C, it is confirmed that MVA treatments tend to have lower costs and potentially reduce a significant cost. Therefore, by looking at both clinical and economic perspectives, improving and strengthening the quality and accessibility of PAC with MVA is a priority.